2013
DOI: 10.1371/journal.pone.0077935
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Restraint Stress Upregulates Erythropoiesis through Glucocorticoid Stimulation

Abstract: In response to elevated glucocorticoid levels, erythroid progenitors rapidly expand to produce large numbers of young erythrocytes. Previous work demonstrates hematopoietic changes in rodents exposed to various physical and psychological stressors, however, the effects of chronic psychological stress on erythropoiesis has not be delineated. We employed laboratory, clinical and genomic analyses of a murine model of chronic restraint stress (RST) to examine the influence of psychological stress on erythropoiesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
18
1
1
Order By: Relevance
“…Irrespective of AVP deficiency, patients with cDI generally have other factors influencing haematopoiesis, for example anterior pituitary deficiency with or without replacement therapy. Although there is evidence that thyroid hormones 18,19 and glucocorticosteroids 20‐22 have an impact on erythropoiesis, we did not find any association of hypothalamic‐pituitary‐thyroid hormone or HPA axis deficiency and altered haemoglobin levels in cDI patients. This is most likely explained by the euthyroid and euadrenal state of our patients under replacement therapy.…”
Section: Discussioncontrasting
confidence: 92%
“…Irrespective of AVP deficiency, patients with cDI generally have other factors influencing haematopoiesis, for example anterior pituitary deficiency with or without replacement therapy. Although there is evidence that thyroid hormones 18,19 and glucocorticosteroids 20‐22 have an impact on erythropoiesis, we did not find any association of hypothalamic‐pituitary‐thyroid hormone or HPA axis deficiency and altered haemoglobin levels in cDI patients. This is most likely explained by the euthyroid and euadrenal state of our patients under replacement therapy.…”
Section: Discussioncontrasting
confidence: 92%
“…The CRS model is known to induce psychological stress and is often used to study depression [ 37 , 38 ]. Although diverse factors contribute to the development of depression, recent research has suggested that neuroinflammation has a significant role in the pathogenesis of depressive disorders [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in serum levels of corticosterone in the disharmony group exceeded the 200 ng/ml threshold considered to reflect ‘stress’ in rodents (Fig. 2 ) 3 , 18 .…”
Section: Discussionmentioning
confidence: 81%